Biosynthesis of catechol melanin from glycerol employing metabolically engineered Escherichia coli. Issue 1 (December 2016) - Mejía-Caballero, Alejandra; Anda, Ramón; Hernández-Chávez, Georgina; Rogg, Simone; Martinez, Alfredo; Bolívar, Francisco; Castaño, Victor; Gosset, Guillermo
Abstract Background Melanins comprise a chemically-diverse group of polymeric pigments whose function is related to protection against physical and chemical stress factors. These polymers have current and potential applications in the chemical, medical, electronics and materials industries. The biotechnological production of melanins offers the possibility of obtaining these pigments in pure form and relatively low cost. In this study, Escherichia coli strains were engineered to evaluate the production of melanin from supplemented catechol or from glycerol-derived catechol produced by anEscherichia coli strain generated by metabolic engineering. Results It was determined that an improved mutant version of the tyrosinase fromRhizobium etli (MutmelA), could employ catechol as a substrate to generate melanin. StrainE. coli W3110 expressing MutmelA was grown in bioreactor batch cultures with catechol supplemented in the medium. Under these conditions, 0.29 g/L of catechol melanin were produced. A strain with the capacity to synthesize catechol melanin from a simple carbon source was generated by integrating the gene MutmelA into the chromosome ofE. coli W3110trpD9923, that has been modified to produce catechol by the expression of genes encoding a feedback inhibition resistant version of 3-deoxy-d -arabino -heptulosonate 7-phosphate synthase, transketolase and anthranilate 1, 2-dioxygenase fromPseudomonas aeruginosa PAO1. In batch cultures with this strain employing complex medium with 40 g/L glycerol as a carbon source, 1.21 g/L of catechol melanin were produced. The melanin was analysed by employing Fourier transform infrared spectroscopy, revealing the expected characteristics for a catechol-derived polymer. Conclusions This constitutes the first report of an engineeredE. coli strain and a fermentation process for producing a catechol melanin from a simple carbon source (glycerol) at gram level, opening the possibility of generating a large quantity of this polymer for its detailed characterization and the development of novel applications.